An exact explicit dual for the linear copositive programming problem - Kostyukova, O. I. (2022)
Recently, for a linear copositive programming problem, we formulated an exact explicit dual problem in the form of the extended Lagrange-Slater dual. This dual problem is formulated using only the data of the primal copositive problem, satisfies the strong duality relation, and is obtained without any regularity assumptions due to the use of a concept of the normalized immobile index set. The constraints of the exact explicit dual problem are formulated in terms of completely positive matrices and their number is presented in terms of a finite integer parameter m_0. In this paper, we prove that m_0≤2n, where n is the dimension of the primal variable’s space.